(untitled) (Theatrum historiae, 2016)
The present paper presents two documents controlling the course of the Bishopric Seminary and the Institute of Theology in Hradec Králové. The documents in question are Institutio seminarii episcopalis Reginae-Hradecensis, the statutes of the seminary issued by bishop Hermann Hannibal Blümegen in 1766, and Institutum seminarii episcopalis Reginæ-hradecii, the statutes created by bishop Tadeas M. Trautmannsdorf in 1802. Studying these normative sources can be a good starting point for our knowledge of the character and the life of the institution. Information on the clerical formation is extremely important for the period of Josephinism when the way and quality of the human life were significantly influenced by the clergy.